القارئ الضمني في "رسالة الغفران" لأبي العَلاء المعريّ / The Implied Reader in the Risalah al-Ghufran of Abu al-‘Ala al-Maʿarri - Mahmoud Karim, Ramadan; Omran Mohammed, Hussien (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2017)
ملخص البحث: بدأت إسهامات آيزر في النظرية النقدية مع شروعه محاضراً في جامعة كونستانس عام 1970م، وقد اشتهر بعد مدة وجيزة بنظريته التجاوب الجمالي وتبعها بعد ذلك بمؤلفينِ آخرينِ هما: (القارئ الضمني)، و(فعل القراءة). يرى آيزر إنّ انتاج المعنى يكون نتيجة التفاعل بين النص والقارئ، ومن ثم قاده ذلك إلى ابتكار مفهوم عملي جديد لرؤيته هو القارئ الضمني، ويعرفه بأنه حالة نصية وعملية انتاج للمعنى على السواء، ومن ثم يسعى البحث إلى الكشف عن القارئ الضمني في رسالة الغفران بوصفه أحد أهم انجازات نظرية القراءة والتلقي. استهل البحث بمقدمة نظرية مكثفة اضاءت فيها تعريفات هذا المفهوم الاجرائي، تلتها محوران، كان الأوّل بعنوان: العلامات الناطقة للقارئ الضمني، وتشمل ثريا النص وتقنيات الإغراب ووجهة النظر الجوالة والديالوج. والثاني، بعنوان مناطق الفراغ والنفي في الخطاب الغفراني، ومن تقنياتها تقطيع السرد وفاعلية التصوير البياني والتناص الأجناسي وخرق المعيار الديني. توصل البحث إلى أنّ من آليات تحديد القصدية هي آليّة الراوي الكلي العلم في السرد بوساطة الإغراب اللغوي، وتكمن أهمية الاسترجاع في المبنى الحكائي لرسالة الغفران بكونها بنية أساسية من بنيات حضور القارئ الضمني، وأن المؤلف الضمني قد أسهم وبفاعلية في تشكيل القارئ الضمني عن طريق خطاباته لغوياً وأدبياً ودينياً واجتماعياً وسياسياً، وأن تحقيق القارئ الضمني كانت بآلية الشخصية الهامشية. الكلمات المفتاحية: القارئ الضمني- رسالة الغفران- أبي العلاء المعري- رسالة أبي العلاء- القارئ. Abstract: The contribution of Wolfgang Iser in theory of literature critic could be noted when he started lecturing in Constance University. He became famous after his esthetical response theory which was followed by another theory; the implied reader and the act of reader theories. Iser thought that the production of meaning is the result of interaction between the text and the reader, and this led him to propose a practical new concept that he termed as ‘the implied reader’ that he defined as textual situation and process of meaning production. This paper tries to uncover the aspect of ‘implied reader’ in the Ghufran Letter of al-Maʿarri which is regarded as the most significant aspect in the theory of reading and reception. The research starts with an introduction to shed lights on this aspect. The introduction is followed by two sections, the first one are the signs of manifestations of the implied reader aspect which includes the text title, defamiliarization techniques, the wondering view point and dialogues; while the second one is entitled the narrative gaps and negation in the text through the techniques such as narrative division, optimizing figurative descriptions, intertextuality through paronomasia and the breakaway rom religious norms. Among the conclusions of the study: among the tools to identify the intentionality of a text is the omniscient narrator whose narration is characterized by language defamiliarization. The importance of retrieval of the narrative structure lies in the forms of the structures that manifest the presence of the implied reader. The implied writer has contributed significantly to the construction of the implied reader through his linguistic, literary, religious, social and political expressions. The construction of the implied reader was through the mechanism of marginal characters. Keywords: Implied reader- Risalah Ghufran- Abu al-‘Ala al-Maʿarri- Letters of Abi ‘Ala- the reader. Abstrak: Sumbangan Wolfgang Iser dalam teori kiritkan sastera mula mendapat perhatian ketikan beliau mula menjadi pensyarah di Universiti Contstance. Beliau menjadi terkenal selepas teori tindak balas estetika yang dikemukannya disamping teori-teori pembaca tersirat and teori tindakan pembaca yang dipeloporinya. Iser melontarkan yang penjanaan makna adalah natijah kepada ineraksi di antara teks dan pembacanya. Ini telah mendorong beliau mengemukakan satu konsep praktikal yang dinamakan beliau sebagai ‘pembaca tersirat’ yang dieertikan beliau sebagai satu keadaan tekstual dan proses penghasilan makna. Artikel ini cuba untuk menyingkap aspek pembaca tersirat ini di dalam Risalah Ghufran karangan al-Maʿarri kerana aspek ini dianggap sebagai yang terpenting dalam teori pembacaan dan penerimaan makna. Kajian bermula dengan pengenalan untuk menjelaskan aspek ini. Ia disusuli oleh dua bahagian: pertama berkenaan tanda-tanda penampilan aspek pembaca tersirat yang merangkumi tajuk teks, teknik penggayaan bahasa luar biasa, perspektif tinjauan dan dialog. Bahagian kedua pula membicarakan tentang jurang naratif dan penafian dalam teks melalui teknik-teknik seperti pembahagian naratif, penggunaan optimum gambaran figuratif, ciri antara teks melalui paronomasia dan pengabaian norma keugamaan. Di antara dapatan kajian ialah: di antara instrumen untuk mengenalpasti aspek tujuan teks ialah pencerita serba tahu yang ungkapan bahasanya berciri keluarbiasaan bahasa. Kepentingan memahami struktur naratif dapat dilihat pada srtuktur-struktur yang berkisar tentang kehadiran pembaca tersirat. Penulis tersirat pula menyumbang terhadap pembentukan pembaca tersirat melalui ungkapan linguistik, saterawi, keugamaan, kemasyarakatan dan politiknya. Pembentukan pembaca tersirat juga adalah melalui pemahaman tentang watak-watak sampingan yang terdapat dalam teks. Kata kunci: Pembaca tersirat- Risalah Ghufran- Abu al-‘Ala al-Maʿarri- Risalah Abi ‘Ala- Pembaca.